Antimicrobial activity of sapindus mukorossi and saponaria officinalis extracts on streptococcus mutans and enterococcus faecalis - Mert Eren, Meltem; Dikmen, Benin; Vatansever, Cansu; Servi, Huseyin; Caner Yegin, Hulki; Ozan, Gunce (Annals of Medical Research, 2021)
Aim: Studies on the antimicrobial effectiveness of saponins against oral pathogens are conflicting. Therefore, this study aimed to evaluate the antimicrobial activity of saponins from three different extracts of Sapindus mukorossi and Saponaria officinalis plants against Streptococcus mutans and Enterococcus faecalis. Materials and Methods: The fruit of Sapindus mukorossi and the root of Saponaria officinalis materials were sliced into small pieces and macerated with hexane, ethyl acetate (EtOAc) and methanol (MeOH), in this order. The antimicrobial activity of the extracts against Streptococcus mutans and Enterococcus faecalis was determined by the broth microdilution method based on the minimum inhibitory concentrations (MIC) of each extract.Results: Except for the hexane extract of Saponaria Officinalis, all extracts of both plants had an inhibitory activity against the tested microorganisms. Higher MIC values were obtained against Enterococcus faecalis than Streptococcus Mutans. The lowest MIC values for both Sapindus mukorossi and Saponaria officinalis were against Streptococcus mutans (4 mg/ml). Conclusion: Saponins extracted from Sapindus mukorossi and Saponaria officinalis have a potential antibacterial activity against oral pathogens. They may be used as an ingredient in dental agents.
Keywords: Antimicrobial activity; emEnterococcus faecalis/em; minimum inhibitory concentration; saponin; emStreptococcus mutans/em